2005
DOI: 10.1007/s00426-005-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tonal and temporal expectations on chord processing and on completion judgments of chord sequences

Abstract: Pitch and time are two principal form-bearing dimensions in Western tonal music. Research on melody perception has shown that listeners develop expectations about "What" note is coming next and "When" in time it will occur. Our study used sequences of chords (i.e., simultaneously sounding notes) to investigate the influence of these expectations on chord processing (Experiments 1 and 4) and subjective judgments of completion (Experiments 2 and 3). Both tasks showed an influence of tonal relations and temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 67 publications
(101 reference statements)
4
63
0
1
Order By: Relevance
“…Major chords were in addition rated higher for consonance and pleasantness than minor chords, and were judged most quickly, corroborating the results of similar experiments that have demonstrated that more expected stimuli are processed more quickly Bigand & Pineau, 1997;Tillmann et al, 2008;Tillmann & Lebrun-Guillaud, 2006). …”
Section: Chords Without and With Musical Contextsupporting
confidence: 85%
“…Major chords were in addition rated higher for consonance and pleasantness than minor chords, and were judged most quickly, corroborating the results of similar experiments that have demonstrated that more expected stimuli are processed more quickly Bigand & Pineau, 1997;Tillmann et al, 2008;Tillmann & Lebrun-Guillaud, 2006). …”
Section: Chords Without and With Musical Contextsupporting
confidence: 85%
“…The current findings are relevant to existing theories of pitch-time integration. Regarding the local/global proposal (Bigand et al, 1999;Jones & Boltz, 1989;Tillmann & Lebrun-Guillaud, 2006), it is important to note that the present experiments always required attention to the entire melody (i.e., global tasks), yet the pattern of pitch-time integration varied. Instead, manipulating instructions affected whether interactions occurred, rather than showing overall evidence of interactions with these global tasks.…”
Section: ---Insert Figure 4 About Here----discussionmentioning
confidence: 93%
“…Given that the cerebellum has also been associated with processing of temporal features (Ivry & Keele, 1989), we are currently investigating whether cerebellar patients are sensitive to temporal manipulations in the musical priming task (cf. Tillmann & Lebrun-Guillaud, 2006, for healthy listeners). The location of cerebellar damage for six of the patients is shown, excepting B5 and M1 for whom reconstructions were not available.…”
Section: Discussionmentioning
confidence: 98%